Exploring the potential impact of household photovoltaic systems on low-carbon production behavior in rural areas: unveiling the pro-environmental spillover effect - Wang, Ying; Wang, Shali; Zhang, Ruohan; Ma, Haijing; Hu, Anjun; Wu, Jiaxi; Yu, Biao; Fan, Shuangshuang (Frontiers in Energy Research, 2024)
Introduction: China, as the world’s largest emitter of carbon dioxide, faces significant challenges in agricultural greenhouse gas emissions. The Chinese government has been actively promoting household photovoltaic (PV) power generation, which has great potential for application in rural areas. This study aims to explore whether the promotion of household PV systems in rural areas has a positive impact on farmers’ low-carbon production behavior and to analyze the influencing factors and mechanisms. This research fills the research gap in the analysis of the promotion of household PV systems and farmers’ low-carbon production behavior, providing scientific evidence to support policymakers in promoting widespread use of household PV systems and facilitating the transition of farmers to low-carbon production methods. Methods: This study adopts a qualitative research method and analyzes interview data and semi-structured questionnaire survey data from 48 farmers. By collecting, organizing, comparing, and extracting information and employing the research process of grounded theory, the researchers summarize the model of household PV-driven low-carbon production behavior. Results: The study finds that the installation of household PV systems indeed promotes farmers to adopt more low-carbon production behaviors. Farmers who install household PV systems show a greater willingness to reduce the use of fertilizers and pesticides, conserve water resources, and improve land utilization, among others. They perceive the positive effects of household PV systems and their own capacity for environmental protection, enhancing confidence and motivation to engage in low-carbon production behaviors. Discussion: Existing research methods have mainly relied on theoretical deduction combined with quantitative empirical approaches when exploring farmers’ pro-environmental spillover behaviors. However, these methods often start from the perspectives of either egoism or altruism, resulting in biased tendencies toward negative spillover or positive spillover. Nevertheless, neither egoism nor altruism fully captures the decision-making process when deeply understanding farmers’ production, life, and decision-making processes. The installation of household PV systems can change factors such as farmers’ knowledge, skills, cognition, and resources, enhancing their green self-efficacy and helping them acquire more knowledge and skills in renewable energy. Therefore, this research adopts a qualitative research method to more accurately reflect farmers’ decision-making process and provides practical recommendations to promote farmers’ active transition to pro-environmental spillover behaviors. Conclusion: This study fills the research gap in the analysis of the promotion of household PV systems and farmers’ low-carbon production behavior, providing practical recommendations for policymakers to facilitate farmers’ positive behavioral changes. Qualitative research methods enable a more realistic understanding and promotion of farmers’ pro-environmental spillover behaviors by deeply understanding their contexts. The study offers targeted suggestions to policymakers to drive farmers’ transition to low-carbon production methods.